Consumer Innovation And Adoption Of Online Shopping: Malaysian Internet User's Perspective - Mohd. Suki, Norazah (2006)
Innovative online shoppers possess certain special characteristics since they have a broad range of online shopping experiences and awareness and hence, are interested online retailer to learn how innovative these customers are. Not many researchers hav ebeen conducted on the innovativeness of online shoppers. The study has been carried out to provide an in-depth knowledge on this issue.